Seven-Year Patterns in US Cigar Use Epidemiology Among Young Adults Aged 18–25 Years: A Focus on Race/Ethnicity and Brand - Jennifer Cullen; Paul Mowery; Cristine D. Delnevo; Jane Allen; Natasha Sokol; Michael Byron; Amber Thornton-Bullock (2011)
We examined patterns in cigar use among young adults, aged 18-25 years, focusing on race/ethnicity and brand.We conducted a secondary data analysis of cross-sectional waves of the National Survey on Drug Use and Health, 2002-2008, using multivariate logistic regression to assess time trends in past 30 days cigar use, past 30 days use of a "top 5" cigar brand, cigar use intensity, and age at first cigar use.Cigar use has increased among White non-Hispanic men aged 18 to 25 years, from 12.0% in 2002 to 12.7% in 2008. Common predictors of all outcomes included male gender and past 30 days use of cigarettes, marijuana, and blunts. Additional predictors of past 30 days cigar and "top 5" brand use included younger age, non-Hispanic Black or White race, lower income, and highest level of risk behavior. College enrollment predicted intensity of use and "top 5" brand use.Recent legislative initiatives have changed how cigars are marketed and may affect consumption. National surveys should include measures of cigar brand and little cigar and cigarillo use to improve cigar use estimates.